Modern drummer magazine emagazine (Modern Drummer Magazine.)
Modern Drummer is the world’s most widely read drum magazine, is dedicated entirely to the art of drumming and caters to the needs of amateur, semi-pro, and professional drummers. Every month MD features entertaining interviews with the world’s most popular drummers from all styles of music; interviews that delve into playing techniques, equipment, and musical concepts. The publication also reports on industry trends and activities, plus new drum products, publications, and recordings, and industry events. A roster of over 35 educational departments, authored by leaders in the field, offers readers practical playing tips and advice on topics that encompass all phases of drumming.